Manajemen Problematika Pelayanan Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kabupaten Rejang Lebong - Syaiful Bahri; Murniyanto Murniyanto; M. Amin (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the problems of service management at the Investment and One-Stop Integrated Service Office (DPMPTSP) of Rejang Lebong Regency. The research method used is qualitative descriptive, with data collection techniques through observation and interviews with the Head of Office, Head of Division, and Licensing Service Staff. The data obtained were analyzed through the stages of collection, reduction, presentation, and drawing conclusions. The results of the study indicate that the main problems in licensing services at the DPMPTSP of Rejang Lebong Regency include the slow licensing process due to the manual system, limited supporting technology, and the minimal number of operators in inputting permits. To overcome this problem, DPMPTSP has implemented various managerial strategies, such as planning based on needs analysis, developing information systems, improving human resource competencies, and implementing digital services to accelerate the licensing process. In addition, the organizational aspect is also a major concern with the formation of integrated service units, the preparation of a clear organizational structure, and strengthening coordination between work units. The implementation of one-stop service-based services and increasing transparency through a digital information system are solutions to improve service efficiency and accessibility. Keywords: Service Management, DPMPTSP, Licensing, Information Technology, One-Stop Service